Violence and gender identity: considerations about girls in the area of health - Kreis, María Manuela; D'Agostino, Agustina María Edna (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2021)
The aim of this article is to introduce some relationships between the historical-social dimension, the current problems related to violence and gender identity in girls, and the health-disease-care process for feminities. From here, we point out that the particularization of girls was historically linked to knowledge-power strategies and to universes of meanings that naturalized gender inequalities from an early age. Likewise, we observe that gender-based violence constitutes a current problem that can have an impact on the health of girls. Finally, we note that along with the emergence of gender identities in childhood, such as trans girls, cissexist practices coexist in health care facilities that need to be questioned.